The Impact of Social Insurance Contributions on Firms Employment and Wages: Evidence from China Employer-Employee Matching Survey Data - Ma, Xinxin; Cheng, Jie (Asian Development Policy Review, 2020)
Using China Employer-Employee Matching Survey (CEES) data from 2014 to 2016, this study examines the influence of social insurance contributions on the levels of employment and the wage levels in Chinese firms. We construct three indices of social insurance enforcement: the city contribution rate (CCR), the rate of city enforcement of social insurance (CE), and the firms’ actual contribution rate (FAR) to employ an empirical study. The new findings are as follows. First, those firms in regions with high city contribution rates or a high rate of city enforcement of social insurance are likely to employ more workers. A bipolarization phenomenon is found in the relation between the firms’ actual social insurance contributions and the adjustments to levels of wage and employment. Second, the impact of social insurance contribution on firms’ level of wages and employment differ by firms’ ownership types, in response to the increased social insurance burden, privately-owned enterprises are more likely to reduce wage levels than the state-owned enterprises.